Knowledge and Attitude towards Do-Not-Resuscitate Order among Nurses of a Tertiary Level Hospital - Shrestha, Asmita; Shrestha, Sarala (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Knowledge regarding and attitude towards end-of-life care can shape the behaviour and actions of a health professional in provision of supportive care for the comfort of the patients as well as their family members. Very little is known about nurses’ knowledge and attitude regarding do-not-resuscitate (DNR) order. Therefore, the purpose of this study was to identify the knowledge of and attitude towards DNR order and relationship between knowledge and attitude towards DNR order among the nurses of a tertiary level hospital. Methods: Descriptive correlation design was used. Convenient sampling method was used to select 70 nurses from a tertiary level hospital. Data were collected using pretested self administered structured questionnaire. Data were analysed using SPSS version 20 and analysed using descriptive and inferential statistics. Result: Among 70 respondents, almost all (95.7%) of the respondents had good level of knowledge, 2.9% had fair and 1.4% had poor level of knowledge. Most (80.0%) of the respondents had positive attitude towards DNR order and 20.0% had negative attitude. There was a positive relationship between knowledge of and attitude towards DNR order (r = 0.068) but the relationship was statistically insignificant. Conclusions: Based on the findings, the study concludes that nurses of tertiary level hospital have good knowledge and positive attitude towards DNR order. Likewise, knowledge regarding DNR order is related with the attitude towards DNR order and thus knowledge can be enhanced to improve the attitude towards DNR by regular in-service education.